Testing and evaluation of electro- vari-focal/chromic lens. (3rd August 2021) - Kim, Tae-Hoon; Kim, Hyun-Jeong; Choi, Dong-Soo; Nah, Yoon-Chae; Kim, Sang-Youn
Abstract: Constructing a compact, simple, lightweight, and universal tuneable lens is challenging. Therefore, this paper suggests a miniature electro-focus/chromic tuneable lens whose focal point and optical transmittance are independently controlled by electric power. The proposed lens uses plasticized poly (vinyl chloride) and electrochromic gels to change its curvature and its brightness according to various electric powers. Due to this effect, we can observe not only the variation of the lens's focal point but also the change of its transmittance. Moreover, as we removed the electric power, the shape of the proposed lens and its transmittance returned back to the initial condition. Through experimentation, the focal length of the proposed lens increased from 5 mm to 14.234 mm when the electric field input was increased, and the transmittance varied from 91.85% to 3.86% with increasing in electric current.